Bioluminescence in cancer research - Applications and challenges - Shrikant B. Mali (Oral Oncology Reports)
Bioluminescence imaging (BLI) is an important technology in preclinical scientific research as well as non-invasive tumour diagnoses. Despite its extensive use, BLI is essentially qualitative, making quantitative measurements and drawing precise conclusions difficult. Technical advancements in BLI have been accomplished through tomographic methods and the connection of these with CT and MRI images. Reconstruction approaches, whether mathematical or AI-based, seek to solve the inverse problem based on optical characteristics and tissue behaviour. BLI is also widely employed in cancer imaging, especially in light of recent advances in genetic engineering, stem cell, and gene therapy therapies. Because of their distinct benefits over standard fluorescent reporters, bioluminescent reporters are increasingly being employed in research. These approaches show how to detect and measure bioluminescence at a low cost utilising conventional tools.